Senescent AECⅡ and the implication for idiopathic pulmonary fibrosis treatment - Zhang, Tingwei; Zhang, Jinjin; Lv, Changjun; Li, Hongbo; Song, Xiaodong (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic and lethal lung disease with limited treatment options. The onset of IPF increases with age, indicating that aging is a major risk factor for IPF. Among the hallmarks of aging, cellular senescence is the primordial driver and primary etiological factor for tissue and organ aging, and an independent risk factor for the progression of IPF. In this review, we focus on the senescence of alveolar type II epithelial cells (AECIIs) and systematically summarize abnormal changes in signal pathways and biological process and implications of senescent AECIIs during IPF progression. Meanwhile, we objectively analyze current medications targeting the elimination of senescent cells or restoration of vitality such as senolytics, senomorphics, autophagy regulators, and stem cell therapy. Finally, we dialectically discuss the feasibility and limitation of targeting senescent AECIIs for IPF treatment. We hope that the understanding will provide new insights to the development of senescent AECII-based approaches for the prevention and mitigation of IPF.